Effect of organoclay on contact angle, thermal and mechanical properties of filled epoxy composites. (2021) - Sabu, M.; Ruban, Y. Jaya Vinse; Ginil, Mon S.
Abstract: In this study, the preparation of organoclay filled hybrid epoxy composites and the hydrophilic, thermo-mechanical behaviour of organoclay with the incorporation of epoxy resin/unsaturated polyester (UP) was analysed. TGA results reveal that the thermal behaviour of the epoxy matrix increases when it is filled with 5% clay and toughened with 5% unsaturated polyester combined with 3% clay. From the DSC data, the maximum glass transition temperature is observed for epoxy matrix with 1% clay and toughened with 5% unsaturated polyester combined with 3% clay. The significant capacity of water repellent property using organoclay is highlighted.